The Effects of Human Resource Management Practices on Organizational Commitment: An Analytical Study of the Ministry of Culture in Jordan - Al afeef, Amjad (The Arab Journal of Administration, 2018)
The aim of this study was to identify the effects of human resources management practices on organizational commitment at the ministry of culture in Jordan. A descriptive analytical approach and a field study were used as main methods to conduct this study. A questionnaire was designed to gather data, which consisted of 58 question measuring all study variables. The questionnaire was distributed to all employees holding supervision and control positions in all ministry centers, counted 58 employees. In total, 56 questionnaires were returned to the researchers and they were useable in the analysis, representing a response rate of 92.7% of the entire study population. The findings of the study showed that participants of the study have a moderate level attitude towards human resource management practices including human resource planning, staffing (recruitment, selection and appointment), compensation and incentives, training and performance appraisal). The study also showed moderate attitudes towards continuance commitment and normative commitment, however, the attitudes towards emotional commitment were low. The findings of the study also showed that Human Resource Management (HRM) has a significant effect on organizational commitment (affective commitment, continuance commitment and normative commitment,) Through value (F) at the level of significance (∞ ≤ 0.05), indicating the significance of the model. Further statistical analysis showed that HRM practices do not individually influence affective commitment, however that entire effect (the relationship) was as a consequence of the interaction of the two variables, as B and T values were all insignificant. In light of the above, this study reveals some recommendation as follows Its necessary for the ministry to pay more attention to HR planning and staffing programs including recruitment, selection and appointment, in order to select the best competent candidates for the advertised job vacancies. The ministry should also pay more attention to providing appropriate compensation and incentives that meet employees ambition and help improve the performance. Moreover, the ministry needs to give more attention to employees’ performance evaluation in a fairer and more transparent manner. Finally, enhance the organizational value systems, create appropriate opportunities, and meet employee’s needs, that help achieve their administrative and financial ambitions, creating thus moral obligation and commitment towards the organization.